Moderate Physical Activity Reduces the Odds of Sarcopenia in Community- dwelling Older Women: A Cross-sectional Study - Gonalves Marini, José A.; Abdalla, Pedro Pugliesi; Bohn, Lucimere; Mota, Jorge; Duncan, Michael; dos Santos, André Pereira; Lopes Machado, Dalmo Roberto (Current Aging Science, 2023)
Introduction: The time spent in different physical activity (PA) intensities is associated with sarcopenia risk for community-dwelling older women. Aim: To evaluate the role of sitting time and physical activity (PA) level as predictors of sarcopenia odds. Methods: In a cross-sectional study, physically independent older women (n = 67) performed the six-minute walk test to identify functional limitation (≤ 400 m). Sedentary time (as sitting time) and PA (light, moderate and vigorous) were obtained with the International Physical Activity Questionnaire (IPAQ). Sarcopenia was diagnosed as recommended by the Society of Sarcopenia, Cachexia and Wasting Disorders (SCWD). Sarcopenia odds (low muscle mass and functional limitation) was predicted by binary logistic regression, considering the weekly sitting time and PA as independent variables. Results: Sarcopenia prevalence was 7.5% (n = 5), with functional limitation present in 38.8% (n = 26), and low muscle mass in 22.4% (n = 15). The predictive model (p = 0.014) involved moderate PA as the only significant predictor (OR = 0.999; p = 0.005; 95% CI: 0.998-1.000) of functional limitation. Moderate PA prevents sarcopenia odds. Each weekly hour of moderate PA decreased sarcopenia odds by 6%. Conclusion: Time spent in moderate PA can prevent sarcopenia.
Keywords: mobility